Laparoscopic Approach in Acute Appendicitis - Teixeira, Nuno (2012)
Background: The appendectomy is the most frequently performed surgery in the Emergency Service. The introduction of the lapa- roscopic approach (LA) in the treatment of acute appendicitis has not received, in the surgical community, the same acceptance that it obtained in other acute conditions. With this work, the authors present the growing acceptance that the LA has been acquiring in the Surgical Service that they represent, and they also want to demonstrate the advantages of this approach towards the laparotomic approach. Materials and Methods: Observational retrospective study consisting of patients undergoing appendectomy for acute appendicitis between 01/11/2008 to 31/10/2010 in the Emergency Service of the CHTS, EPE. Results: In the presented series 477 patients were subjected to an appendectomy, 9,6% of which through an LA. For both surgical approaches, the average age was 33,1 years (CI 91%:29,6-37,4) to LA and 37,3 years (CI 91%:31,7-38, 9) to laparotomic approach, p = 0,11; the female gender represented 19,0% of patients undergoing LA and 42,0% of patients undergoing laparotomy, p = 0,03. The duration of the hospital stay in LA was 3,2 days (CI 91% :2,4-4, 0) and 4,2 days (CI 91%:3,9-4, 4) in the laparotomic approach, p = 0,041 ; postoperative complications occurred in 7,7% of patients undergoing laparotomy and 8,7% of patients receiving LA, p = 0,8. There was no mortal- ity in this series.Conclusions: The LA, in the treatment of acute appendicitis, increased considerably over the two years of the study. It allows better cosmetic results and shorter hospital stay. It revelas a complication rate similar to the one of the laparotomic approach and can be used safely in patients with complicated acute appendicitis.  Keywords: acute appendicitis, appendectomy, laparoscopic approach